Magic Formula: Can It Be Used to Identify 'Winning Stocks' in the Indonesian Stock Exchange? - Michael, Michael; Sasmitapura, Angga; Faninda, Sandra; Fransisca, Elza; Setiawan, Amelia (International Journal of Pertapsi, 2024)
Magic Formula, developed by Joel Greenblatt, offers a simplified investment model that can be used by individuals without extensive financial literacy. This model uses two key metrics: return on capital and earnings yield, to identify potentially profitable stocks. This study tests the effectiveness of the Magic Formula using data from companies listed on the Indonesia Stock Exchange over the past ten years (2011-2021). The results indicate that the Magic Formula yields an average annual return of 39.81%, significantly outperforming the market return, which stands at 6.16%.